(untitled) (Conference Zone, 2022)
The article describes the theory and practice of applying the basic principles of managerial activity related to specific aspects of social interactions between individuals, social groups in society and its subsystems in various social organizations. In our research work, ideas were put forward on creating an effective working environment, information support for management, strategic management, risk management, conflict management, emergency management.